The Role of Bali's Traditional Subak Farming System in the Preservation of Natural and Cultural Resources - Ardana, Putu Doddy Heka; Suparwata, Dewa Oka; Sudrajat, Arief; Chatun, Sri; Harsono, Iwan (Westscience Press, 2024)
The Subak traditional farming system in Bali embodies a harmonious relationship between humans, nature, and spirituality, epitomizing the Balinese philosophy of